Clinical prediction scores and the utility of time to blood culture positivity in stratifying the risk of infective endocarditis in Staphylococcus aureus bacteraemia. (15th April 2022) - Simos, Peter A; Holland, David J; Stewart, Adam; Isler, Burcu; Hughes, Ian; Price, Nathan; Henderson, Andrew; Alcorn, Kylie
Abstract: Background: Infective endocarditis (IE) complicates up to a quarter of Staphylococcus aureus bacteraemia (SAB) cases. Risk scores predict IE complicating SAB but have undergone limited external validation, especially in community-acquired infections and those who use IV drugs. Addition of the time to positive culture (TTP) may provide incremental risk prognostication. Objectives: To externally validate risk scores for predicting IE in SAB and assess the incremental value of TTP. Methods: The modified Duke score was calculated for adults hospitalized with SAB at a major tertiary institution. All patients underwent echocardiography. Sensitivity and specificity of the risk scores for predicting IE were calculated, and the incremental value of TTP was assessed. Results: One hundred and six cases were analysed and 18 (17%) met definite IE criteria. The optimal TTP to predict IE was 11.5 h (sensitivity 88.9%; specificity 71.6%). The sensitivity of VIRSTA and PREDICT (Predicting risk of endocarditis using a clinical tool) were similar (94.4% for both) and higher than POSITIVE (Prediction Of Staphylococcus aureus Infective endocarditis Time to positivity, IV drug use, Vascular phenomena, pre-Existing heart condition; 77.8%). The receiver-operator characteristic AUCs were VIRSTA 0.83, PREDICT 0.75, POSITIVE 0.89 and TTP 0.85. Adding TTP to VIRSTA (i.e. VIRSTA+) resulted in the highest AUC (0.90), sensitivity (100%) and negative predictive value (100%), albeit with a low specificity (33%). Conclusions: The VIRSTA and POSITIVE scores were the strongest predictors for IE complicating SAB. The addition of TTP to VIRSTA (VIRSTA+) significantly improved discriminatory value and may be safely used to rationalize echocardiography strategies.